2012
DOI: 10.1111/j.1399-3054.2011.01554.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and control of Genipa americana seed germination

Abstract: Genipa americana (Rubiaceae) is important for restoration of riparian forest in the Brazilian Cerrado. The objective was to characterize the mechanism and control of germination of G. americana to support uniform seedling production. Morphology and morphometrics of seeds, embryo and endosperm were assessed by light and scanning electron microscopy during germination. Imbibition and germination curves were generated and over the same time interval endosperm digestion and resistance were measured by puncture for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
7

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 40 publications
2
9
0
7
Order By: Relevance
“…Means followed by identical letters in the same column do not differ each other by Tukey post-hoc comparison (P < 0.05). dormancy in the seeds of some species (Bewley 1997;Gong et al 2005;Queiroz et al 2012), our results indicated the important role of this enzyme in storage mobilization and endosperm weakening -allowing haustorium expansion during seedling development (a post-germination event).…”
Section: Discussionsupporting
confidence: 58%
“…Means followed by identical letters in the same column do not differ each other by Tukey post-hoc comparison (P < 0.05). dormancy in the seeds of some species (Bewley 1997;Gong et al 2005;Queiroz et al 2012), our results indicated the important role of this enzyme in storage mobilization and endosperm weakening -allowing haustorium expansion during seedling development (a post-germination event).…”
Section: Discussionsupporting
confidence: 58%
“…Falls in ABA were probably related to imbibition effects, in agreement with Ali-Rachedi et al (2004). ABA inhibits the synthesis and action of cell wall hydrolases (Amaral da Silva et al 2008;Queiroz et al 2012), and during imbibition these enzymes can mobilise storage products. Tissues surrounding the embryo are sites of cell wall loosening by mannanases, galactosidases and mannosidases, which can also provide mechanical defence (Bewley et al 2013).…”
Section: Discussionmentioning
confidence: 56%
“…; Queiroz et al . ), and during imbibition these enzymes can mobilise storage products. Tissues surrounding the embryo are sites of cell wall loosening by mannanases, galactosidases and mannosidases, which can also provide mechanical defence (Bewley et al .…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted by Queiroz et al (2012), demonstrated that one of mechanisms contributing to slow and uneven germination of G. Americana, is related to strength imposed in the micropylar endosperm preventing the expansion and elongation radicle. Therefore, the main enzyme involved in the weakening of the micropylar endosperm (endo-β-mannanase) it has its activity increased when the seeds are soaked in water.…”
Section: Pre-soaking In Distilled Watermentioning
confidence: 99%